Nonlinear Fourier analysis of matter-wave soliton interferometry - Feng, Yu-Jie; Sun, Zhi-Yuan; Yu, Xin (Frontiers in Physics, 2023)
The bright solitons in quasi-1D atomic Bose-Einstein condensates are good candidates for constructing matter-wave interferometers with high sensitivity and long phase-accumulation times. Such interferometers at the mean-field level can be theoretically studied within the framework of quasi-1D Gross-Pitaevskii (GP) equation with narrow repulsive potential barriers. In this paper we present a basic proposal of using the nonlinear Fourier transform (NFT), also known as the inverse scattering transform, as an effective tool to analyze the soliton contents for those interferometers, which thanks to the nearly integrable nature of the GP equation when the normalized atom number fraction near the barrier is small. Based on typical cases, we show that the soliton components can be accurately detected from the output wave fields of the interferometers by computing the NFT spectra.